2018
DOI: 10.3390/magnetochemistry4010005
|View full text |Cite
|
Sign up to set email alerts
|

Switching Magnetic Properties by a Mechanical Motion

Abstract: Switching magnetic properties have attracted a wide interest from inorganic chemist for the objectives of information storage and quantum computing at the molecular level. This review is focused on magnetic switches based on a mechanical motion, which is an innovative approach. Three main strategies to control magnetic properties by a mechanical motion have been developed in the literature and will be described. The first one (ligand-induced spin change) consists in modulating the ligand field strength by a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 78 publications
(94 reference statements)
1
12
0
Order By: Relevance
“…Actually, fragmentation appears to be the rule rather than the exception on metals, and consequently further investigations in that direction have already started. Different strategies are explored in parallel, consisting in the synthesis of more robust compounds [25] and the development of new spin switching designs involving mechanical motion [102][103][104] or hydrogen abstraction [105,106]. In addition, SCO complexes incorporating a functional switchable ligand have been reported [44] and hold great promises.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, fragmentation appears to be the rule rather than the exception on metals, and consequently further investigations in that direction have already started. Different strategies are explored in parallel, consisting in the synthesis of more robust compounds [25] and the development of new spin switching designs involving mechanical motion [102][103][104] or hydrogen abstraction [105,106]. In addition, SCO complexes incorporating a functional switchable ligand have been reported [44] and hold great promises.…”
Section: Discussionmentioning
confidence: 99%
“…Molecules exhibiting switchable magnetic properties have been extensively studied over the last few decades in the context of the miniaturization of electronics, sensors, and memory devices. This particular field of magnetic switching has been the subject of major developments fueled by numerous research activities focused on molecular spin crossover (SCO) materials and single-molecule magnets. Most examples described so far are crystalline solids obtained from first-row transition-metal complexes ( d 4 to d 7 ) capable of undergoing spin-state transition as a response to external physical perturbations such as temperature, pressure, and light. ,, From a practical point of view, SCO phenomena are quite often difficult to explain from well-defined molecular events and they are also strongly dependent on cooperativity processes that happen to be enhanced in the solid state and at low temperatures. , SCO systems are therefore usually studied in solid crystals, although recent reports have shown that similar processes can occur in solution and at near-ambient temperatures. , …”
Section: Introductionmentioning
confidence: 99%
“…Among all types of spin transition (ST), the first-order spin crossover, which has a large hysteresis width and a transition temperature T 1/2 at room temperature, has the most potential for application. Since most ST cannot directly meet the actual application, it is an urgent task to study the possibility of precise regulation of ST. The use of both various external physical stimuli, such as temperature, pressure, , light, magnetic field, , and X-ray radiation, and chemical, such as the structural modification and replacement of coordinated metal ligands, organic radicals, or metals, can change the properties of the complex in a wide range and then regulate the ST phenomenon.…”
Section: Introductionmentioning
confidence: 99%